Bioresorbable scaffolds for the treatment of coronary artery disease: current status and future perspective. (September 2014) - Kraak, Robin P; Grundeken, Maik J; Koch, Karel T; de Winter, Robbert J; Wykrzykowska, Joanna J
<x xml:space="preserve">Abstract</x> Bioresorbable scaffolds represent a novel approach in the treatment of coronary artery disease which allows for vessel wall support without leaving a permanent foreign body in the coronary artery. This technology has the potential to reduce some of the shortcomings of current standard treatment with metallic drug-eluting stents, such as late in-stent restenosis, impaired vasomotion of the stented segment and hindrance of surgical revascularizations. Currently, several bioresorbable scaffolds are available and undergoing clinical or preclinical evaluation. This review will present the current status of development of bioresorbable scaffolds, describe the degradation/resorption process of each device and the clinical data available to date.